ANALISIS METODE PENGOLAHAN DATA KASUS OUTAGE TRANSMISI SERAT OPTIK: STUDI KASUS JARINGAN TIGA REGION - Angela Aneke Putri Saraswati; Annisa Sarah (Jurnal Elektro, 2020)
The wide implementation of fibre optic transmission cable supports the increasing demand of datacommunication, due to its reliability and its fast connectivity. However, optical fibre communicationmight experience an outage condition, which could degrade the overall network performance. Thisstudy analyses an eight months data recording of outage tickets for three region networks by usingTableau. We study three main parameters: age of nodes, device models and the number of tickets thataffect the number of outages in each region. Based on these parameters, we identify the top prioritymaintenance nodes in each region that affect the performance the most. We classified the outagecondition based on internal (e.g. breaker down, maintenance), and external (e.g. electricity blackout,cable bitten by animals). Study shows that most outage causes are the “Electricity blackout” whichaccount of 33.33% of total cases. Meanwhile, the region that suffered by outage the most is Jakarta-Central, with only 99,74% Network Availability (NA), compared to Jakarta-Bekasi-Karawang withNA 99,85% and Jakarta-NorthEast with NA 99,86%.